Examining Model Development of Physics Learning through Multi-intelligence to Nurture Autonomous Learners - Zainuddin Zainuddin; Alimuddin Mahmud; Muris Muris (Intelektual Pustaka Media Utama, 2017)
This study aims at examining a model of learning physics through multi-intelligence, which are valid, practical, and effective to enhance learners’ autonomy. The authors developed instruments and learning media to obtain a valid, practical, and effective model using research and development design. The results showed that this lack of autonomy of learners in learning physics. The experiment showed that the physics learning through multi-intelligence met the criteria of valid, practical and effective. All the aspects of physics learning with multi-intelligence run well. The ability of teachers to manage learning was at the high category. The physics learning with multi-intelligence was in the medium category. The activities of learners in learning fulfilled the ideal time and learners responded positively to the learning model of physics through multi-intelligence.